Detailed Calorimetric Analysis of Mixed Micelle Formation from Aqueous Binary Surfactants for Design of Nanoscale Drug Carriers - Ádám Juhász; László Seres; Norbert Varga; Ditta Ungor; Marek Wojnicki; Edit Csapó (Nanomaterials, 2021)
While numerous papers have been published according to the binary surfactant mixtures, only a few articles provide deeper information on the composition dependence of the micellization, and even less work attempts to apply the enhanced feature of the mixed micelles. The most important parameter of the self-assembled surfactants is the critical micelle concentration (cmc), which quantifies the tendency to associate, and provides the Gibbs energy of micellization. Several techniques are known for determining the cmc, but the isothermal titration calorimetry (ITC) can be used to measure both cmc and enthalpy change (ΔmicH) accompanying micelle formation. Outcomes of our calorimetric investigations were evaluated using a self-developed routine for handling ITC data and the thermodynamic parameters of mixed micelle formation were obtained from the nonlinear modelling of temperature- and composition- dependent enthalpograms. In the investigated temperature and micelle mole fractions interval, we observed some intervals where the cmc is lower than the ideal mixing model predicted value. These equimolar binary surfactant mixtures showed higher solubilization ability for poorly water-soluble model drugs than their individual compounds. Thus, the rapid and fairly accurate calorimetric analysis of mixed micelles can lead to the successful design of a nanoscale drug carrier.